2014
DOI: 10.4103/1658-354x.140864
|View full text |Cite
|
Sign up to set email alerts
|

Combined spinal and general anesthesia is better than general anesthesia alone for laparoscopic hysterectomy

Abstract: Context:Spinal anesthesia (SA) was combined with general anesthesia (GA) for achieving hemodynamic stability in laparoscopic hysterectomy.Aims:The aim of our study was to evaluate the impact of SA combined with GA in maintaining hemodynamic stability in laparoscopic hysterectomy. The secondary outcomes studied were requirement of inhaled anesthetics, vasodilators, and recovery profile.Settings and Design:We conducted a prospective, randomized study in ASAI/II patients posted for laparoscopic hysterectomy, who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Poonam S. Ghodki et al compared the effect of 10mg bupivacaine heavy intrathecally along with general anaesthesia alone for laparoscopic hysterectomy. It was found that a statistically significant rise in mean arterial blood pressure (113.40 ± 4.06 v/s 92.42 ± 2.72, p=0.001) 12 continued throughout pneumoperitoneum when general anaesthesia only was given. After the release of pneumoperitoneum, the difference was not statistically significant and blood pressure values were within 20% of baseline.…”
Section: Discussionmentioning
confidence: 96%
“…Poonam S. Ghodki et al compared the effect of 10mg bupivacaine heavy intrathecally along with general anaesthesia alone for laparoscopic hysterectomy. It was found that a statistically significant rise in mean arterial blood pressure (113.40 ± 4.06 v/s 92.42 ± 2.72, p=0.001) 12 continued throughout pneumoperitoneum when general anaesthesia only was given. After the release of pneumoperitoneum, the difference was not statistically significant and blood pressure values were within 20% of baseline.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies were based on subjective survey studies 8 . In this study, we performed an objective study by calculating anthropometric measurements and intra‐abdominal volumes.…”
Section: Discussionmentioning
confidence: 99%
“…7 In a subjective evaluation of surgeons in a study showing the curative effect of SA combined with GA on hemodynamic parameters, it has been observed that a better operating area is formed by contracting the intestines and pulling them upward as a result of the increase in parasympathetic activity following SA. 8 In this study, our assumption was that as a result of the sympathectomy effect of SA to be performed simultaneously with GA, we would obtain a wider operation area with the same pressure with a decrease in muscle tone and pulling the intestines up. Moreover, we wanted to demonstrate this by making anthropometric measurements and calculating the volume of intra-abdominal insufflated CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…SA alone is being successfully utilized for short or day care laparoscopic procedures. For major laparoscopic surgeries, however, conventional GA is still the technique of choice [16] . But under GA, the hemodynamic derangements during pneumoperitoneum have to be managed by either increasing the anesthetic concentration or by administering vasodilators [17,18] .…”
Section: Discussionmentioning
confidence: 99%